An experimental study on the impact of two dimensional materials in waste disposal sites: What are the implications for engineered landfills? (2016)
It is generally accepted that landfilled municipal solid waste develops a heterogeneous and anisotropic structure during placement, degradation and settlement. Flow and transport processes, in traditional and alternative landfills, are strongly influenced by the type of structure developed. The presence of preferential flow has gained research interest, given its impact on landfill processes. This paper describes an experimental investigation carried out on a specimen of degraded municipal solid waste. Preferential flow was detected and caused by the specimen layered structure composed of two dimensional particles derived from less easily degradable materials such as plastics, textiles and paper which made up more than 50% of the specimen dry mass. The results suggest that two dimensional particles play a role in promoting preferential flow because they modify flow paths and increase the tortuosity. A high content of less easily degradable two dimensional materials suggests incompatibility with better management practices, seeking a more even distribution of fluids to enhance degradation and faster stabilisation rates within engineered landfills. Consequently, there is a need to re-think the types and quantities of materials that are restricted under current landfill policies. © 2016 Chinese Institute of Environmental Engineering, Taiwan